HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT ANTIHIPERTENSI PADA PASIEN PROLANIS LANSIA DI WILAYAH KERJA PUSKESMAS TAMBAK KABUPATEN BANYUMAS - Amalia, Ary Nahdiyani; Fitriyani, Novita Endang; Arfani, Anun (Medical and Health Journal, 2024)
Family is a factor that has a big impact on compliance because it will motivate sufferers to be more confident when dealing with the health problems they are experiencing. This study aims to determine the relationship between support provided by the family and compliance with hypertension treatment in elderly prolanis patients at Tambak 1 and 2 Community Health Centers. The study design used was cross-sectional analytical observation. The research began in April-May 2023 at Tambak 1 and 2 Community Health Centers and was conducted on 92 patients. Data were collected using a questionnaire and Spearman's Rho testing was carried out. The results of the study showed a value of p = 0.002 (p < 0.05), which means that there is a significant relationship between family support and compliance with taking medication for elderly prolanis patients at Tambak 1 and 2 Community Health Centers. The correlation coefficient (r) was obtained at 0.321 and the direction of the relationship obtained a positive r value, meaning that the more the family supports the sufferer, the higher the degree of compliance with treatment. The conclusion that can be drawn is that compliance with hypertension treatment is closely related to the support provided by family members of elderly prolanis patients at Tambak 1 and 2 Community Health Centers. The Community Health Center can provide information, education or health counseling to hypertension prolanis participants about the importance of hypertension treatment compliance and the role of the family. in providing support to maintain stable blood pressure in prolanis patients.